Kill Bill : Vol. 2 - Tarantino, Quentin; Daryl, Hannah; David Carradine; Julie Dreyfus; Lucy LiuVivica A Fox; Michael Madsen; Uma Thurman (USA Miramax Films, 2003)
""The Bride"" was once part of a group of world class female assassins, until the group leader, ""Bill"" and the other assassins turn against her. Five years later ""The Bride"" awakens from the coma the assassins left her in and heads out to seek bloody revenge. Unlike conventional movies, Kill Bill is told in chapter format making the narrative flow more like a book than a film.
The Bride wakes up after a long coma. The baby that she carried before entering the coma is gone. The only thing on her mind is to have revenge on the assassination team that betrayed her - a team she was once part of.
Quentin Tarantino
Languages: Turkish, English
Subtitles: Turkish, English
Keywords: Crime; Drama; Thriller; Action